The Face of Workplace Violence: Experiences of Healthcare Professionals in Surgical Hospital Wards - Jenny Jakobsson; Malin Axelsson; Karin Örmon (Hindawi Limited, 2020)
Background. Though workplace violence (WPV) is a global problem for healthcare professionals, research within in-hospital care has mainly focused on WPV in emergency healthcare settings. Thus, the number of qualitative studies that explores experiences of WPV in general hospital wards with a longer length of stay is limited. Aim. The aim of this study was to explore how healthcare professionals in surgical hospital wards experience and manage WPV perpetrated by patients or visitors. Method. The study applied a qualitative, inductive approach using focus group interviews for data collection. A purposeful sample of 16 healthcare professionals working in surgical wards was included. Data were analysed using a thematic analysis. Findings. The analysis resulted in four main themes: workplace violence characteristics, partly predictable yet not prevented, approaching workplace violence, and consequences from workplace violence. During the focus group interviews, the healthcare professionals described various acts of physical violence, verbal abuse, and gender discrimination perpetrated by patients or their visitors. Despite the predictability of some of the incidents, preventive strategies were absent or inadequate, with the healthcare professionals not knowing how to react in these threatful or violent situations. They experienced that WPV could result in negative consequences for the care of both the threatful or violent person and the other patients in the ward. WPV caused the healthcare professionals to feel exposed, scared, and unprotected. Conclusion and clinical implications. Exposure to WPV is a problem for healthcare professionals in surgical wards and has consequences for the patients. Preventive strategies, guidelines, and action plans are urgently needed to minimise the risk of WPV and to ensure a safe work and care environment.